Myostatin and related proteins on the control of skeletal muscle mass and capillary density - Moreira Soares Oliveira, Bernardo (2013)
Skeletal muscle wasting is a feature of many pathological conditions such as muscular dystrophies, cancer and diabetes. Human ageing also results in the progressive loss of muscle mass and strength, a condition known as sarcopenia (or myopenia). Therefore, interventions that can reverse or slow down muscle loss are highly desirable. The TGF-β member myostatin is a well-known inhibitor of skeletal muscle growth, but it may also, if deleted, decrease muscle oxidative capacity. We have used the activin receptor 2B (ActR2B) fused to the Fc region of immunoglobulin G (ActR2B-Fc) as a trap to sequester myostatin and inhibit its activity. We sought to evaluate possible differences between doses and frequency of injection, as well as the signalling pathways involved in the response. For this purpose, healthy C57-BJ mice (n = 5-6 per group) were injected with either 5 or 10 mg/kg ActR2B-Fc once or twice a week for 2 weeks. PBS-injected mice served as controls. Gastrocnemius cryosections were immunostained for sarcolemma (caveolin 3) and capillaries (isolectin). Image analysis (fibre cross-sectional area (CSA) and capillary density) was done using ImageJ. Protein synthesis was measured by puromycin incorporation, and protein expression and phosphorylation were measured by western blotting. After 2 weeks of treatment we found increased muscle masses and fibre CSA irrespective of dose and frequency of injection. Muscle capillary density (per area) decreased dose-dependently. To study the mechanisms involved mice were injected with a single (10 mg/kg) dose of ActR2B-Fc one or two days before sacrifice. Muscle rpS6 phosphorylation, a marker of mechanistic target of rapamycin (mTORC1) activity, increased 2 days after injection. Accordingly, muscle protein synthesis increased ~30% 2 days after injection. The phosphorylation status of ERK, a MAPK member involved in angiogenesis, decreased in muscle 2 days after injection. These signalling responses were no longer observed after 2 weeks. In conclusion, the present study showed that 2 weeks of ActR2B-Fc administration increased muscle mass and fibre CSA, while reducing capillary density and oxidative metabolism. Combining ActR2B antagonism with other interventions that may attenuate the reduction in capillary density and oxidative metabolism (such as exercise) may yield more desirable outcomes.